Detection of broad spectrum beta-lactamase ESBLs in multiresistant Pseudomonas aeruginosa using ESBLs CHROM agar. (Journal of the College of Basic Education, 2022)
(75) isolates of Pseudomonas aeruginosa bacteria were obtained out of (100) isolates collected from various pathological conditions, including wounds, burns, middle ear infections, and urine and blood samples.An antibiotic sensitivity test was conducted for (12) antibiotics belonging to the beta-lactam group, and the isolates showed a clear variation in their antibiotic resistance, as they were resistant to (Ampicillin; Carbencillin; Cephalexin; Cefotaxime; Ceftriaxone; Amoxicillin/clavulanic) by (100)%, while it showed resistance to an antibiotic. Ceftazidime by (81.33)% and to Cefepime by (70.66)%; The isolates showed the least resistance to Piperacillin by (37.33)%, to Meropnem by (33.33)%, to Aztreonam by (22.66%) and to Imipenem by (17.33%).The result of detecting the production of beta-lactamase enzymes by the isolates showed that (56) isolates were producing beta-lactamase enzymes, with a rate of (74.66%). While the detection result showed